Interaction between a surface acoustic wave and adsorbed atoms - Peleshchak, R.M.; Seneta, M.Ya. (Condensed Matter Physics, 2016)
Within nonlocal elastic interaction between an adsorbed atom and matrix atoms and in consideration of the
mirror image forces, a dispersion law of elastic surface acoustic waves is found to the long-wavelength approximation depending on the concentration of adsorbed atoms and the deformation potential of the adatom. The
energy width of the surface acoustic mode is calculated depending on the concentration of adsorbed atoms. У межах нелокальної пружної взаємодiї адсорбованого атома з атомами матрицi з врахуванням сил дзеркального зображення знайдено в довгохвильовому наближеннi закон дисперсiї поверхневих пружних
акустичних хвиль в залежностi вiд концентрацiї адсорбованих атомiв i деформацiйного потенцiалу адатома. Розраховано енергетичну ширину поверхневої акустичної моди в залежностi вiд концентрацiї адсорбованих атомiв.